ADOPTING OSMAN WARNING IN INDONESIA: AN EFFORT TO PROTECT POTENTIAL VICTIMS OF CRIME TARGET - Taufiqurrohman, Moch. Marsa (Jurnal Hukum dan Peradilan, 2022)
In the development of criminal law globally, experts believe that preventing crime is much better than taking action. This article exemplifies several criminal cases, especially serial murder cases in Indonesia, which show the lack of quality in the crime prevention system in Indonesia. In line with these consequences, this article considers that Indonesia needs a kind of â€œwarningâ€ system to increase efforts to prevent crimes. Furthermore, this article refers to the experience of implementing the Osman Warning in the UK, improving the quality of crime prevention. This article concludes that there are many problems in the crime prevention system in Indonesia. In responding to these problems, this article aims to answer three concerns. First, what are the difficulties in preventing crime in Indonesia? Second, what is the extent of the obligations of law enforcement in preventing crimes? Third, what is the probability of adopting the Osman Warning concept in Indonesia? Furthermore, this article claims that the probability of implementing the Osman Warning in Indonesia is relatively high and is suitable for implementation. Finally, this article provides a view that special regulations are needed in the laws and rules to accommodate the Osman Warning in the criminal law system in Indonesia.